TMIC-37. INTERCELLULAR COMMUNICATION BETWEEN NORMAL AND TUMOR CELLS IN GLIOMA MICROENVIRONMENT. (11th November 2019) - Hossain, Anwar; Hasan, Irtiza; Adachi, Satoshi; Ledbetter, Daniel; McDonald, Malcolm; Gumin, Joy; Daou, Marc; Phillips, Lynette; Parker-Kerrigan, Brittany; Lang, Frederick
Abstract: The interactions between tumors cells and their microenvironment are increasingly recognized as contributors to tumor growth and therapeutic resistance in glioblastoma (GBM). Mesenchymal Stem Cells (MSCs) have been implicated as components of the microenvironment of several cancers, but their contribution to GBM remains obscure. Recently we reported that GBMs contain cells resembling human mesenchymal stem cells, called Glioma-associated-MSCs (GA-hMSCs), based on our ability to isolate these cells from patient tumors (Figueroa, et al. Can Res 2017. 77, 5808–5819). In order to characterize the function of these cells in vivo, we used a PDGFRb promoter driven mouse model to track and modulate the behavior of endogenous MSCs (PDGFRb + cells). To generate tumors that mimic gliomas, we injected the RCAS-PDGF avian retrovirus into PDGFRb EGFP/nTVA mice. These mice express EGFP in PDGFRb expressing cells and RCAS receptor TVA under the control of the Nestin promoter and develop tumors. Immunostaining these tumors for GFP and CD31 determined that MSC like cells reside around blood vessels and are likely the major contributor of microvascular proliferation often seen in human gliomas. Additionally, we sought to see if there was communication between MSCs localized around blood vessels and the tumor. To this end, mice with Cre recombinase expression under the PDGFRb promoter were implanted with a GL-261 tumor harboring a dsRed/eGFP Cre recombinase/LoxP site. In these mice, tumor color change from red to green indicates transfer of Cre mRNA or protein from PDGFRb+ cells (MSCs) to tumor cells (GL-261dsRed/eGFP). We observed red to green transition in tumors, indicating that there is transfer of mRNA or protein, and further suggesting that there is direct communication between the tumor microenvironment and the tumor. Taken together, our findings emphasize the crucial role of MSCs in the tumor microenvironment.